1990
DOI: 10.1002/j.1460-2075.1990.tb07439.x
|View full text |Cite
|
Sign up to set email alerts
|

A new homeotic mutation in the Drosophila bithorax complex removes a boundary separating two domains of regulation.

Abstract: The bithorax complex specifies the identity of parasegments 5‐14 of Drosophila. Although nine parasegment‐specific functions, abx/bx, bxd/pbx and iab‐2 to iab‐8,9 have been identified, the whole bithorax complex appears to encode only three classes of proteins, Ubx, abd‐A and Abd‐B. Many observations suggest that the parasegment‐specific functions act as positive cis‐regulatory elements of Ubx, abd‐A and Abd‐B. We report the molecular genetics of a new gain‐of‐function mutation, Fab‐7, which transforms paraseg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
193
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(204 citation statements)
references
References 34 publications
(37 reference statements)
3
193
0
1
Order By: Relevance
“…Alternatively, mod protein may bind boundary DNA sequences in order to insulate decondensed transcriptionally active domains. Such a role for boundary sequences has been proposed to explain the developmental regulation of the Drosophila Bithorax complex (Gyurkovics et al, 1990) and the expression of a reporter gene subjected to position effect (Kellum and Schedl, 1991). Based on its developmental expression pattern and the requirement for mod demonstrated by genetic analysis, we hypothesize that the transcriptional control of target genes mediated by the mod gene product is required for a normal morphogenesis of endo -mesodermal and cephalo-pharyngeal structures.…”
Section: Discussionmentioning
confidence: 94%
“…Alternatively, mod protein may bind boundary DNA sequences in order to insulate decondensed transcriptionally active domains. Such a role for boundary sequences has been proposed to explain the developmental regulation of the Drosophila Bithorax complex (Gyurkovics et al, 1990) and the expression of a reporter gene subjected to position effect (Kellum and Schedl, 1991). Based on its developmental expression pattern and the requirement for mod demonstrated by genetic analysis, we hypothesize that the transcriptional control of target genes mediated by the mod gene product is required for a normal morphogenesis of endo -mesodermal and cephalo-pharyngeal structures.…”
Section: Discussionmentioning
confidence: 94%
“…Genetic, transgenic, and molecular studies have identified a number of classes of distinct cis-regulatory elements within the iab regions capable of directing abdA and AbdB expression. Insulator DNAs have been identified at the boundaries of the iab8-iab7 domains (Frontabdominal-8, Fab8) (4), iab7-iab6 domains (Fab7) (5)(6)(7)(8)(9)(10), and iab5-iab4 domains (Miscadastral pigmentation, Mcp) ( Fig. 1 A) (7,11).…”
Section: E Xpression Of the Abdominal-a (Abda) And Abdominal-b (Abdb)mentioning
confidence: 99%
“…Indeed, we were able to isolate ry+ transformants at the normal frequency, if we inserted into the same construct between the IAB5 fragment and the ry+ gene an 'insulation' sequence known to interfere with enhancer -promoter interactions (suppressor-of-Hairy-wing protein binding sites; Dorsett, 1990;Holdridge and Dorsett, 1991 (Lewis, 1978;Karch et al, 1985;Gyurkovics et al, 1990;see Figure 1). These are gain-of-function mutations: Mcp causes ectopic expression ofAbd-B protein in ps9 in a pattern and at a level similar to that normally found in pslO (Celniker et al, 1990;Sanchez-Herrero, 1991), whereas the phenotype of Fab implies that Abd-B protein is expressed more strongly in psl1, at the level normally found in ps12 (Gyurkovics et al, 1990 Figure 1) did not show any enhancer activity in transformed embryos (see above), we wondered whether they may have silencing activity. We linked either of these fragments to the BXD enhancer and the Ubx proximal promoter and tested the combination constructs (called MB and FB) for (-gal expression in transformed embryos.…”
Section: The Iab5 Patternmentioning
confidence: 99%
“…To answer this, we decided to study the properties of transcriptional control regions within Abdominal-B (Abd-B), another homeotic gene located within the bithorax complex (Salnchez-Herrero et al, 1985). This gene is unique among Drosophila homeotic genes as it contains two separable genetic subfunctions, called m and r, which control morphogenesis in different posterior domains of the larva and the adult (Casanova et al, 1986): m function is required in parasegments (ps) 10-13, whereas r function is required in ps14 (Casanova et al, 1986; see also Karch et al, 1985;Tiong et al, 1985; Celniker and Lewis, 1987 (Karch et al, 1985;Gyurkovics et al, 1990). Underneath proteins which share the same homeodomain, but whose expression is controlled by different promoters (SanchezHerrero and Crosby, 1988;Celniker et al, 1989;DeLorenzi et al, 1988;Kuziora and McGinnis, 1988;Zavortink and Sakonju, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation